2007
DOI: 10.1111/j.1365-2648.2006.04088.x
|View full text |Cite
|
Sign up to set email alerts
|

Role development and career stages in addiction nursing: an exploratory study

Abstract: Identification of these five role development stages for addiction nurses offers employers, nurse managers, educators and addiction nurses a starting point from which specific occupational competencies can be further explored. In addition, continuing professional development needs can be mapped to specific role development stages. Employers and nurse managers may wish to offer increased learning opportunities to student nurses to gain work experience within specialist addiction units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
1
15
0
1
Order By: Relevance
“…The findings of the present study are also consistent with Clancy et al (2007) with regard to the nurses' role in treating alcohol dependency, as addiction is a specialized area and often not included in nursing education and practice. The nurses participated in the present study perceived the nature of addiction as complicated, which can be compared with previous findings that described addiction work as 'robust and hardy' (Clancy et al, 2007). The skills used in this specific area include knowledge of interpersonal developmental theories and counseling, as well as the biological and medical aspects of treating addiction.…”
Section: Appropriateness Of Western Models In a Thai Settingsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings of the present study are also consistent with Clancy et al (2007) with regard to the nurses' role in treating alcohol dependency, as addiction is a specialized area and often not included in nursing education and practice. The nurses participated in the present study perceived the nature of addiction as complicated, which can be compared with previous findings that described addiction work as 'robust and hardy' (Clancy et al, 2007). The skills used in this specific area include knowledge of interpersonal developmental theories and counseling, as well as the biological and medical aspects of treating addiction.…”
Section: Appropriateness Of Western Models In a Thai Settingsupporting
confidence: 93%
“…Communication difficulties are a major hindrance in providing care for people experiencing addiction, since most patients deny their addictions (Wadell & Skärsäter, 2007). When working in alcohol addiction services nurses need specific skills, such as developing therapeutic alliance and providing counseling (Clancy, Oyefeso, & Ghodse, 2007). Although specific methods such as MI can be learned during nursing education programs, the knowledge will rapidly dissipate in the absence of a supervisory practice (Schwalbe, Oh, & Zweben, 2014).…”
Section: Factors Affecting the Alcohol Addiction Treatmentmentioning
confidence: 98%
“…With respect to clinical and practice implications, the findings from the present study support alcohol and drug group therapy as a cost‐effective treatment modality within outpatient service provision, including adolescents with conduct disorder involved in the YDC. Lastly, they provide important information for mental health nurses who work in a variety of treatment settings and are involved in assessment and treatment planning with adolescents who experience a complex array of substance use and coexisting mental health, education/vocational, and social issues (Clancy et al . 2007).…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Reay and colleagues 33 explored the managers' roles or perspectives when introducing an NP role into the health care team and found that managers played a key role in the introduction of NP roles in health care teams. Other researchers 15,[36][37][38] have identified the need for managers to have a clear vision for the new APN role that is introduced, facilitate communications with groups involved with the new role, and garner support for the role within the organization. They include task reallocation, the management of altered working relationships, and ongoing management of the team in an evolving situation.…”
Section: Health Care Teammentioning
confidence: 99%